Evolution of the Bureau of Reclamation: an insider historian's perspective on the legacy and the challenge - Storey, Brit Allan, author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 2002)
A paper presented by Brit Allan Storey at the Colorado Water Workshop, Gunnison, Colorado, July 31, 2002.
Listed online under Additional publications list as no. 2.
Keywords: United States. Bureau of Reclamation -- History -- Congresses; Water resources development -- West (U.S.) -- History -- Congresses